Running across Europe : the rise and size of one of the largest sport markets - Scheerder, Jeroen, 1974-; Breedveld, Koen, 1964-; Borgers, Julie, ....- (Basingstoke [England] ; New York : Palgrave Macmillan, 2015)
Over the past forty years, running has developed into one of the most popular physical leisure activities in Europe. An estimated 50 million Europeans are engaged in running as a way to stay healthy and/or to challenge themselves and there has been a marked surge in running events all over Europe with more people running marathons than ever before. Analysing in-depth data from over 11 European countries – including Belgium, Denmark, England, Finland, Germany, Greece, Hungary, the Netherlands, Slovenia and Spain – this collection explores this phenomenon and addresses issues of participation, governance, cost, health and the history of running. Drawing on this unique material, the volume sets out policy challenges and marketing possibilities for maximising the current opportunities provided by the running market.
Keywords: Lopen